Make millions selling on QVC : - Romer, Nick (Wiley, 2008)
Make Millions Selling on QVC is more than just a guide to getting you and your products in front of millions of potential customers; it’s an inside look at how the largest television retailer in the world operates. The information and advice found throughout these pages will give you a distinct edge in this competitive business and allow you to exceed your professional expectations and enjoy the success you deserve.